Time Course of Physiological and Psychological Responses in Humans during a 20-Day Severe-Cold–Acclimation Programme - Brazaitis, Marius (Public Library of Science, 2014)
The time course of physiological and psychological markers during cold acclimation (CA) was explored. The experiment included 17 controlled (i.e., until the rectal temperature reached 35.5°C or 170 min had elapsed; for the CA-17 session, the subjects (n = 14) were immersed in water for the same amount of time as that used in the CA-1 session) head-out water immersions at a temperature of 14°C over 20 days. The data obtained in this study suggest that the subjects exhibited a thermoregulatory shift from peripheral-to-central to solely central input thermoregulation, as well as from shivering to non-shivering thermogenesis throughout the CA. In the first six CA sessions, a hypothermic type of acclimation was found; further CA (CA-7 to CA-16) led to a transitional shift to a hypothermic–insulative type of acclimation. Interestingly, when the subjects were immersed in water for the same time as that used in the CA-1 session (CA-17), the CA led to a hypothermic type of acclimation. The presence of a metabolic type of thermogenesis was evident only under thermoneutral conditions. Cold-water immersion decreased the concentration of cold-stress markers, reduced the activity of the innate immune system, suppressed specific immunity to a lesser degree and yielded less discomfort and cold sensation. We found a negative correlation between body mass index and Δ metabolic heat production before and after CA.